De l’amour et de l’argent. Écriture féminine et réécriture contestatrice : les deux épouses de Mr. Rochester - Anne-Marie Baranowski (Revue LISA)
Wide Sargasso Sea (1966) stands in a particular relationship to Jane Eyre, being neither a sequel nor an inverted chronology nor a palimpsest filling the blanks left by the earlier text. It totally recreates the character of Rochester’s first wife, turning her into an interesting, intelligent woman defeated by adverse circumstances. Thus, Jean Rhys creates a counterpart to the character of Jane Eyre and expresses her own anger and frustration regarding both the English mores and the habits of the male gender. However the novel is not a mere settling of score, because beyond their differences both writers share a number of pivotal themes, which are the subject of this comparative study: 1) the power of money; 2) the complexity and ambiguity of womanhood; 3) the failure of masculinity.